Construction of Bored Piles In Limestone Area and Friction & Point Bearing Capacity Based On Field Test (Osterberg Test) - Adrian , Teh Kim Yoon (IRC, 2016)
The purpose of this research is the identify the effective modified deep foundation; bore piling procedures on top of identifying the special custom made drilling tools that effectively enhance a pile's quality in terms of verticality, besides reducing its construction time and costs; in karstic limestone bedrocks. Moreover, this study will also come out with a general normalized shaft displacement versus shaft resistance graph for the area of Kuala Lumpur, to be used in bored pile design calculations. Over the years bore piling in karstic limestone had always poses tremendous challenges, not only to the contractor itself, but also been a major challenge in bore pile designs. Hence, in order to improve one's productivity in construction, more research regarding bored pile construction has to be done.